Thermosensitive hydrogels for sustained-release of sorafenib and selenium nanoparticles for localized synergistic chemoradiotherapy. (September 2019) - Zheng, Lan; Li, Chang'e; Huang, Xiaoting; Lin, Xueran; Lin, Weiqiang; Yang, Fang; Chen, Tianfeng
Abstract: In this study, we synthesized a thermosensitive composite of Gel-SOR-LUF-SeNPs to achieve the localized synergistic chemoradiotherapy of hepatocellular carcinoma (HCC). Sorafenib (SOR) is one of the important clinical drugs for unresectable and advanced HCC. However, the uncontrollable release of SOR induced drug resistance and severe side effects. Recently, thermosensitive hydrogels have emerged as promising drug-delivery carriers, due to their superior advantages including biodegradability, low-toxicity, high drug loading, site-specificity, sustained and controlled drug release behavior. We synthesized the thermosensitive hydrogel nanosystem (Gel-SOR-LUF-SeNPs) as an effective drug release depot with the combination of radiotherapy for the localized and sustained treatment of HCC. The results showed that SOR was released continuously from Gel-SOR-LUF-SeNPs with the degradation of the hydrogel for a prolonged period (over 15 days). The combination of localized and chemoradiotherapy accelerated the apoptosis of HepG2 cells through reducing the expression of Ki67 and CD34, and activating caspase-3 signaling pathway. Further studies demonstrated that this nanosystem showed site-specific and long-term anticancer effects in mice up to 21 days after single subcutaneous injection, and no obvious side effects of mice were found. Taken together, this study presents a local and long-term treatment for HCC, which may shed light on unresectable HCC therapy in the future. Graphical abstract: Here, we reported a thermosensitive composite of Gel-SOR-LUF-SeNPs for the localized synergistic treatment of hepatocellular carcinoma (HCC). The composite was injected into HepG2 tumor-bearing nude mice in the state of solution to form hydrogel for long-acting therapy with the degradation of PLGA-PEG-PLGA.Image 1